Caracterização epidemiológica dos microrganismos presentes em jalecos dos profissionais de saúde - Marlene da Dores Medeiros (2011)
The identification of possible microorganism reservoirs in healthcare institutions represents an important measure for the prevention of their dissemination. The present study aimed to determine the epidemiological characteristics of microorganisms present in the coats of health professionals in a general hospital. A cross-sectional study was performed from January to August 2011 in a general hospital from Divinópolis. Healthcare professionals who work in the hospital rooms of medical-surgical clinics were included in this study. The inclusion criterion for participants was the act of providing direct medical assistance to patients. For this study, a questionnaire comprised of closed questions referring to the demographic profile, knowledge and behavior of health professionals, was applied. After completing the interview, microbiological samples were collected from the pockets and abdomen regions of the coats using the swab rolling technique. The collected samples were cultivated in sheep blood agar medium, MacConkey agar, Manitol salt agar, Sabourad agar, and thioglucolate broth at 35°C for 72 hours. The isolates underwent species identification using an automated method and were submitted to an antibiogram by means of the disc diffusion method. Analyses were carried out in the institutions clinical analysis and microbiology laboratory. To analyze the data, descriptive statistics, together with the calculation of absolute and relative frequencies, were used. The statistical differences were evaluated by means of a Pearson chi-squared test, maintaining a significance level of 5% (p < 0.05). One hundred professionals, distributed in the categories of nursing team (76.0%) and doctors/physical therapists (24.0%), participated in this study. The work shift for the majority of the participants was the day shift (57.0%). As regards the professionals behavior, 90.0% affirmed that they circulate using the coat in areas outside the hospital rooms (dining hall, snack bar), in care support services, and in administrative areas. The majority of the professionals reported the habit of changing the coat for each shift (68.0%). Concerning the reason why they use the coat, 83.0% cited individual protection. Of the professionals who work in other healthcare locations, 41.2% use the same coat in specific institutions, and 98.0% believe that the coat may in fact contain microorganisms. The positives samples, with recovering of microorganisms, represented 51.0% in the pocket and 43.0% in the abdominal region. The Staphylococcus spp proved to be the most prominent genre in all analyzed areas. Enterococcus faecalis and Acinetobacter baumannii were predominantly found in the abdominal region. Coagulase-negative Staphylococcus proved to be resistant to oxacillin; Acinetobacter baumannii to aminoglycosides, cephalosporins, and quinolones; and Enterococcus faecalis to aminoglycosides and quinolones. Regarding the contamination Staphylococcus coagulase negative of the analyzed areas, a significant difference (p < 0.05) could be observed for the variables of frequency with which the coat was changed, age, and profession. It could be concluded that the coats of healthcare professionals are contaminated by microorganisms of epidemiological relevance, contributing, for the possible spread of pathogens among patients and environments. Therefore, it could be suggested the investment in permanent educational programs geared toward the aspects of biosafety, hand hygiene, and the role of the environment and, including the coats like a potential reservoir of microorganisms.